Nonvisualization of Sentinel Lymph Nodes by Lymphoscintigraphy in Primary Cutaneous Melanoma: Incidence, Risk Factors, and a Review of Management Options. Issue 4 (October 2018) - Pavri, Sabrina Nicole; Gary, Cyril; Martinez, Rajendra Sawh; Kim, Samuel; Han, Dale; Ariyan, Stephan; Narayan, Deepak
Abstract : Background: Lymphoscintigraphy is often performed before sentinel lymph node biopsy, especially in areas likely to have multiple or aberrant drainage patterns. This study aims to determine the incidence and characteristics of melanoma patients with negative lymphoscintigraphic findings and to review the management options and surgical recommendations. Methods: This is a retrospective study of patients with primary cutaneous melanoma who underwent sentinel lymph node biopsy between 2005 and 2016. Patients with nonvisualized lymph nodes on preoperative lymphoscintigraphy were compared in a 1:4 ratio with a randomly selected unmatched cohort drawn from all melanoma patients who underwent preoperative lymphoscintigraphy within the period of the study. Demographic, clinical, and outcome data were compared between these groups. Results: A negative lymphoscintigraphic scan was seen in 2.3 percent of all cases (25 of 1073). In both univariate and multivariate analyses, predictive patient- and tumor-specific factors for negative lymphoscintigraphy included older age and head and neck location. Patients with a nonvisualized sentinel lymph node had significantly worse overall survival compared with patients who had a visualized sentinel lymph node, but there was no difference in melanoma-specific survival. In 16 of the 25 cases (64 percent), at least one sentinel lymph node was found intraoperatively despite the negative lymphoscintigraphic findings. Conclusions: Older patients with head and neck melanomas are more likely to experience nodal nonvisualization on lymphoscintigraphy. In patients who have nodal nonvisualization, the surgeon should attempt sentinel lymph node biopsy at the time of excision of the primary lesion because a sentinel lymph node can still be found in a majority of cases, and it offers prognostic information. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.